Post-thrombotic syndrome, functional disability and quality of life after upper extremity deep venous thrombosis in adults - Kahn, Susan R.; Elman, Elyssa A.; Bornais, Chantal; Blostein, Mark; Wells, Phillip S. (Thrombosis and Haemostasis, 2005)
The post-thrombotic syndrome (PTS) after upper extremity deep venous thrombosis (UEDVT) has not been well characterized. The objective of our study was to describe and quantify residual symptoms, functional disability and quality of life associated with PTS after UEDVT in adults. Twenty-four patients with objectively diagnosed UEDVT (bilateral in 1 patient) at least 6 months previously were recruited from two Canadian thrombosis clinics. Data were collected on demographic characteristics, DVT risk factors and affected venous segments. The Villalta PTS scale, modified for the upper extremity, was used to diagnose PTS. Patients completed questionnaires on degree of functional disability (DASH questionnaire), and generic (SF-36) and disease-specific (VEINES-QOL) quality of life. Results were compared in patients with and without PTS. Patients were assessed a median of 13 months after the diagnosis of UEDVT. Daily ipsilateral arm or hand swelling was reported by 52% of patients and daily ipsilateral arm pain by 20% of study patients, compared with 0% and 0%, respectively, in the contralateral arm. PTS was present in 11/25 (44%) limbs (11/24 patients). One patient had severe PTS. Patients with PTS, compared with those without PTS, had significantly more functional disability (mean DASH score 20.9 vs. 3.7, p= 0.009) and poorer quality of life (mean VEINES-QOL score 45.6 vs. 53.6; p=0.001; mean SF-36 Physical Component Score (PCS) 40.8 vs.50.2; p= 0.12). PTS scores were higher and quality of life was poorer when PTS involved the dominant arm. In conclusion, PTS occurs frequently after UEDVT and is associated with significant functional disability and reduced quality of life. Patients with dominant arm PTS appear to fare worse than those with non-dominant arm PTS. Larger, prospective studies to identify prognostic factors that lead to PTS after UEDVT are warranted.
Keywords: Venous thrombosis; upper extremity; post-thrombotic syndrome; quality of life; symptoms; disability; adults